Paralympic VR Game Immersive Game using Virtual Reality Technology - Macedo, Raquel Duarte (2019)
Throughout the years virtual reality has been used for a wide range of applications, and several types of research have been made in order to improve its techniques and technology. In the last few years, the interest in virtual reality has been increasing partially due to the emergence of cheaper and more accessible hardware, and the increase in content available. One of the possible applications for virtual reality is to lead people into seeing situations from a different perspective, which can help change opinions. This thesis uses virtual reality to help people better understand paralympic sports by allowing them to experience the sports’ world from the athletes’ perspective. For the creation of the virtual environment, both computer-generated elements and 360 video are used. The integration of these two components presented a challenge to explore. This thesis focused on wheelchair basketball, and a simulator of this sport was created resorting to the use of a game engine (Unity 3D). For the development of this simulator, computer-generated elements were built, and the interaction with them implemented. Besides allowing the users to play the sport as if they are in the athlete’s shoes, users can also watch 360 videos in which explanations of the modality (rules and classification) are presented. They are also capable of interacting with some of these videos through virtual elements that are placed over the videos. User studies were conducted to evaluate the sense of presence, motion sickness and usability of the system developed. The results were positive although there are still some aspects that should be improved.